Pengaruh Penggunaan Metode Pembelajaran Inkuiri Terhadap Hasil Belajar Dan Motivasi Siswa - Mbari, Maria A. F.; Yufrinalis, Marianus; Nona, Theresia (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2018)
This study aims to determine the effect of the use of inquiry learning methods on the learning outcomes of fifth grade students in science subjects of light traits in Catholic Elementary School Nita I. This research is a quasi-experimental study. The sample of this study was 39 students consisting of 20 VA students as the experimental class and 19 VB students as the control class. Learning outcomes tests and learning motivation questionnaire sheets were used to obtain data in this study, with a t-test performed to test hypotheses preceded by a prerequisite analysis test in the form of a normality test. The results of this study indicate that the implementation of the inquiry learning method has a positive and significant effect on the students’ learning outcomes. The group of students who took part in the learning with inquiry learning method obtained a better post test score which was equal to 76.25 compared to the group of students who followed conventional learning who obtained a post-test average score of 65.26.